The Influence of Transformational Leadership Style and Compensation on Motivation and Its Impact on Employee Performance at Petrochina International Jabung Ltd - Sari Oktriyani; Saiyid Syekh; Osrita Hapsara (Dinasti Publisher, 2025)
The success of a business organization, company, or industry depends on the performance of its employees. Human resources are a crucial factor in achieving company goals, therefore, human resource development planning is a crucial aspect of achieving these goals. This study aims to determine and describe the state or picture of transformational leadership style, compensation, motivation, and employee performance at Petrochina International Jabung Ltd., as well as to determine and analyze the influence of transformational leadership style and compensation on motivation and its impact on employee performance at Petrochina International Jabung Ltd. This study uses descriptive verification research. The PLS analysis method is used. Based on the descriptive analysis of the research variables, the total score for the transformational leadership style was 4096, categorized as good. Furthermore, the compensation variable showed that employee compensation at PetroChina International Jabung Ltd. was good, with a score of 3117. Furthermore, the motivation variable showed a score of 3616, categorized as high. Meanwhile, the employee performance variable showed a score of 2592, categorized as high. The results of the study indicate that transformational leadership style and compensation have a positive and significant influence on employee motivation and performance at PetroChina International Jabung Ltd. The transformational leadership style can increase employee work motivation, which ultimately impacts their performance. Similarly, adequate compensation has been shown to boost employee motivation and directly improve performance. In addition to their direct influence, transformational leadership style and compensation also have an indirect influence on performance through motivation, meaning motivation mediates the relationship between the two on employee performance.